Acknowledgement of manuscript reviewers 2015 - Pieroni, Andrea (J Ethnobiol Ethnomed, 2016)
The editors of Journal of Ethnobiology and Ethnomedicine would like to thank all our reviewers who have contributed to the journal in Volume 11 (2015).